2017
DOI: 10.4103/ijri.ijri_260_16
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided percutaneous radiofrequency ablation of osteoid osteoma: Our experience in 87 patients

Abstract: Purpose:To evaluate the technical and clinical success of radiofrequency ablation of osteoid osteoma and analyze the factors responsible for clinical success. We also tried to investigate the role of follow-up computed tomography (CT) imaging.Materials and Methods:This is a prospective study approved by the institute's ethics committee involving 87 patients with appendicular osteoid osteoma. CT-guided radio frequency ablation was performed using a bipolar ablation system. Patients were followed up over 15.4 (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…Percutaneous RFA-treatment is an outpatient procedure that does not require large dissections or bone excisions. This makes percutaneous interventional treatments advantageous 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 17, 18, 20, 21. Since the most of our patients were admitted from far-cities, we hospitalised them for one night for close follow-up of possible complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Percutaneous RFA-treatment is an outpatient procedure that does not require large dissections or bone excisions. This makes percutaneous interventional treatments advantageous 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 17, 18, 20, 21. Since the most of our patients were admitted from far-cities, we hospitalised them for one night for close follow-up of possible complications.…”
Section: Discussionmentioning
confidence: 99%
“…The median volume of the lesions was 185 mm 3 (min:22 mm 3 (7 × 3 x 2 mm); max:1123 mm 3 (15 × 12 × 12 mm)). In Pinto, Cagal and Vanderschueren's studies multiple probe usage was suggested for large lesions 7, 8, 22. Since the active tip part of the RFA probe we used was adjustable to 1, 1.5 and 2 cm, we were able to treat lesions of any sizes with single intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that 67% of the tumors developed in the proximal phalanx, 22% in the middle phalanx, and 11% in the metacarpal (21). The involvement of the skull and facial bones is exceptionally rare (22,23).…”
Section: Epidemiologymentioning
confidence: 99%
“…16 Contrast-enhanced CT and MRI although not necessary show enhancement of the unmineralised nidus and helps in increasing the diagnostic accuracy in indeterminate cases. 3 Dynamic CE MRI shows typical kinetic features of nidal enhancement and further helps in diagnosis and localisation of osteoid osteoma 17 (Figure 2e). Technetium (Tc) 99 bone scintigraphy findings of high central uptake with surrounding less uptake, commonly termed as "double density" sign, depicts nidus osteoblastic activity with associated host bone response.…”
mentioning
confidence: 99%